Simon Leys : Navigator Between Worlds. - Paquet, Philippe (Schwartz Publishing Pty. Ltd, 2017)
Simon Leys is the pen-name of Pierre Ryckmans, who was born in Belgium and settled in Australia in 1970. He taught Chinese literature at the Australian National University and was Professor of Chinese Studies at the University of Sydney from 1987 to 1993. He died in 2014.Writing in three languages - French, Chinese and English - he played an important political role in revealing the true nature of the Cultural Revolution. His writing on China and on varied literary and cultural topics appeared regularly in the New York Review of Books, Le Monde, Le Figaro Littéraire, Quadrant and the Monthly, and his books include The Hall of Uselessness, The Death of Napoleon, Other People's Thoughts and The Wreck of the Batavia & Prosper. In 1996 he delivered the ABC's Boyer Lectures. His many awards include the Prix Renaudot, the Prix Mondial Cino Del Duca, the Prix Guizot and the Christina Stead Prize for fiction.This substantial biography - recently published by Gallimard in France to wide acclaim and winning an award from the Académie Francaise - draws on extensive correspondence with Ryckmans, as well as his unpublished writings. It has been translated by an internationally renowned French translator Julie Rose (based in Sydney).